Green Concrete Made From Iron Slag Waste - Mulyatun, Mulyatun (Journal Of Natural Sciences And Mathematics Research, 2015)
Synthesis of green concrete has been carried out by using iron slag waste of PT Inti Jaya Steel Jrakah, Semarang. Geopolimer (green concrete) is an aluminosilicate inorganic polymer with chain Si-O-Al that can be synthesized from material rich in silica and alumina with sodium hydroxide as an activator. Iron slag chemical content analysis indicated that this material is a part of pozzolan material with each individual components weight as follow: SiO2: 4.55%, Al2O3: 2.54%, CaO: 11.43%, Fe2O3: 77.10%, MnO2: 1.43 and  other minerals:  4.07%. The mole ratio of SiO2/Al2O3 of iron slag waste of PT Inti Jaya Steel Jrakah, Semarang is quite high at 3.05. Although the ratio is high, it is still can be synthesized using an activator solution of NaOH and increasing the drying time to 3 days and 24 hours of curing time at 60°C temperature to help the process of water molecule condensation in the geopolymerisation process. Characterized concrete (green concrete) that has been formed shows that the maximum compressive power can be achieved at composition ratio of Iron slag/ Na-silicate /NaOH /H2O of 55/10/4/8, with compressive power of 11.254 MPa. © 2015 JNSMR UIN Walisongo. All rights reserved.